Victor Grant Collection, Album 5, Photograph 292 Frederick Wilder Brooks
Wedding picture taken in 1900.
Designation 5.292 in listing stands for Album 5, Photograph 292.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Brooks, Frederick Wilder; Brooks family. -- New Mexico; Genealogy - Photographic collection